A brain imaging repository of normal structural MRI across the life course: Brain Images of Normal Subjects (BRAINS) - Job, Dominic E.; Dickie, David Alexander; Rodriguez, David; Robson, Andrew; Danso, Sammy; Pernet, Cyril; Bastin, Mark E.; Boardman, James P.; Murray, Alison D.; Ahearn, Trevor; Waiter, Gordon D.; Staff, Roger T.; et al. (NeuroImage (Orlando, Fla.), 2017)
The Brain Images of Normal Subjects (BRAINS) Imagebank (http://www.brainsimagebank.ac.uk) is an integrated repository project hosted by the University of Edinburgh and sponsored by the Scottish Imaging Network: A Platform for Scientific Excellence (SINAPSE) collaborators. BRAINS provide sharing and archiving of detailed normal human brain imaging and relevant phenotypic data already collected in studies of healthy volunteers across the life-course. It particularly focusses on the extremes of age (currently older age, and in future perinatal) where variability is largest, and which are under-represented in existing databanks. BRAINS is a living imagebank where new data will be added when available. Currently BRAINS contains data from 808 healthy volunteers, from 15 to 81years of age, from 7 projects in 3 centres. Additional completed and ongoing studies of normal individuals from 1st to 10th decades are in preparation and will be included as they become available. BRAINS holds several MRI structural sequences, including T1, T2, T2* and fluid attenuated inversion recovery (FLAIR), available in DICOM (http://dicom.nema.org/); in future Diffusion Tensor Imaging (DTI) will be added where available. Images are linked to a wide range of ‘textual data’, such as age, medical history, physiological measures (e.g. blood pressure), medication use, cognitive ability, and perinatal information for pre/post-natal subjects. The imagebank can be searched to include or exclude ranges of these variables to create better estimates of ‘what is normal’ at different ages. •Brain Images of Normal Subjects (BRAINS) image-bank integrated repository project•Sharing and archiving of brain imaging and relevant phenotypic data•Linked textual data e.g. age, history, blood pressure, and cognitive ability•Living image-bank where new data will be added when available.•MRI sequences T1, T2, T2*, FLAIR, and DTI, in DICOM